Kehujjahan Hadis Wasiat dalam Upaya Reaktualisasi Hukum Islam - Hafisuddin; Khairul Bahri Nasution (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article explains the custom of Indonesian society that many parents, when they are still alive, say the sentence to give land, rice fields or houses to their children. This sentence has caused differences in understanding. Some people interpret it as a will that must be carried out after a parent dies, while other people understand it not as a will, but as a form of